Analisis Penerapan Uji Kompetensi Mahasiswa Menyiapkan Tenaga Kerja Profesional Industri Pariwisata upaya keberlanjutan di Indonesia - Shella Gherina Saptiany; Dyan Triana Putra; Nina Mistriani; Wan Norshariza Binti Kamarulzaman; Azizah Naharia; Isnu Hadi Sunarko (BADAN PENERBIT STIEPARI PRESS, 2025)
The rapid growth of Indonesia's tourism industry demands the availability of professional human resources with competencies that are in accordance with the needs of the world of work. In response to these challenges, the Indonesian College of Tourism Economics (STIEPARI) Semarang has established a strategic collaboration with Mahsa University Malaysia in implementing a community service program that focuses on improving student readiness through competency tests and curriculum alignment based on industry needs. This program is carried out through a series of activities, including career development seminars, professional certification training, curriculum evaluation workshops, and direct visits to various tourism industry institutions. This approach aims to strengthen students' practical skills, increase confidence, and encourage active involvement in the practice-based learning process. The results of the activity showed a significant increase in students' readiness to face the world of work, both from technical aspects and soft skills. The curriculum is evaluated and harmonized to become more relevant, flexible, and responsive to the dynamics of the global tourism industry. In addition, this program strengthens the implementation of the Independent Learning-Independent Campus (MBKM) policy by providing space for students to learn directly from the world of work and build professional networks. The implications of this activity are not only improving the quality of graduates, but also strengthening the position of higher education institutions in building sustainable international partnerships. This cross-country collaboration is a model for the development of tourism education that is adaptive, innovative, and oriented to industry needs, while supporting national competitiveness in the tourism sector.